Markets changing, changing markets: Institutional work as market shaping. (September 2019) - Baker, Jonathan J.; Storbacka, Kaj; Brodie, Roderick J.
There is increasing interest in the marketing discipline to adopt an institutional perspective when examining markets. This requires seeing markets as complex systems that evolve through time, rather than as preexisting, stable structures. Using a historical, longitudinal case study, we integrate the "institutional work" framework as a lens to understand the process of market change in the novel, historic case of circus in North America through the 20th century. We explore the decline of the market for traditional American circus, and the emergence, in the 1970s, of the adjacent market for new circus, with a specific focus on the world's preeminent new circus company, Cirque du Soleil . Theoretical contributions of the article include a "market-shaping activities" framework that illustrates market shaping involves considerably more actors than the dyad of producer and consumer. Market-shaping occurs through an interdependent process involving institutionalized practices, beliefs and expectations, and the intentional activities of market actors at any institutional level. Market change is shared, iterative, and recursive, that is cocreated, and undertaken by market actors both formal and informal. Market shapers do not necessarily work in an orchestrated fashion; nevertheless, vibrant networks of complementary actors contribute positively to the construction of shared identities and normative networks. From a managerial perspective, we find implications for policy makers, funders, strategists, and marketers.